An Examination of Misogynistic Hadiths and Their Problems in the Perspective of Women's Human Rights Protection - Muhammad Ilham Barizi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
This article examines hadiths that are considered misogynistic in the Islamic tradition and their problems in the context of protecting women's human rights. Through a literature study approach and qualitative analysis, this research highlights how a literal understanding of some traditions can reinforce negative stereotypes against women and hinder the fulfillment of their rights in various aspects of life. A number of traditions that are often used as arguments to justify gender inequality, such as the prohibition of women's leadership, the assumption of weak reason and religion, and absolute obligation in husband-wife relations, are traced back through analysis of their sanad and socio-historical context. The findings of this study show that many traditions accused of being misogynistic are not meant to be norm-setting but are contextualized or even derived from weak narrations. By integrating a human rights perspective, this article encourages religious reinterpretations that are more just, egalitarian and in line with constitutional principles and international commitments to gender equality and even justice. This study is expected to strengthen the human rights-based religious literacy movement and become a reference for academics, religious leaders, and policy makers.